2019
DOI: 10.3390/microorganisms7090352
|View full text |Cite
|
Sign up to set email alerts
|

The Architecture of Monospecific Microalgae Biofilms

Abstract: Microalgae biofilms have been proposed as an alternative to suspended cultures in commercial and biotechnological fields. However, little is known about their architecture that may strongly impact biofilm behavior, bioprocess stability, and productivity. In order to unravel the architecture of microalgae biofilms, four species of commercial interest were cultivated in microplates and characterized using a combination of confocal laser scanning microscopy and FTIR spectroscopy. In all the species, the biofilm b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 50 publications
3
30
0
Order By: Relevance
“…This is also in agreement with what was postulated by Schnurr et al 39 , which proposed that the most active layers are present in the superficial portion of phototrophic biofilms. Besides, the different relationships (linear and exponential) between the attenuated light by the biofilms and their mean and max thickness suggest heterogeneity of cell density and structure within the biofilms 9 which impacted light attenuation. To the best of our knowledge, only few studies reported about the relationship between light attenuation and structural parameters in microalgae biofilms 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is also in agreement with what was postulated by Schnurr et al 39 , which proposed that the most active layers are present in the superficial portion of phototrophic biofilms. Besides, the different relationships (linear and exponential) between the attenuated light by the biofilms and their mean and max thickness suggest heterogeneity of cell density and structure within the biofilms 9 which impacted light attenuation. To the best of our knowledge, only few studies reported about the relationship between light attenuation and structural parameters in microalgae biofilms 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The confocal microscope set-up was similar to that described in Fanesi et al 9 . Briefly, the images were acquired using an inverted Zeiss LSM700 confocal microscope (Carl Zeiss microscopy GmbH, Jena, Germany) equipped with a LD Plan-Neofluar 20×/0.4 Korr M27 objective with a 0.4 N.A.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those factors, the impact of light, nutrients availability, temperature, pH and shear stress on growth rate and productivity have been studied, but mostly over long-term period of development (i.e. from weeks to months) [6,[19][20][21]. On the other hand, other factors such as substrate properties (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…diatoms) was reported as the dominant species on fouling release and antifouling coatings 34,39 . The four strains can develop biofilm in laboratory tests 40,41,42 , which is why they are currently used as model micro-organisms in the study of molecules or coatings with antibiofilm activities 43,44,45,46,47 . In these studies, P. purpureum is particularly notable due to its resistance to anti-biofilm molecules.…”
Section: Introductionmentioning
confidence: 99%